Management Strategies to Optimize Student Admissions in Higher Education: A Data-Driven Perspective - Mutmainnah Mutmainnah; Agus Timan; Okik Dwi Cahyani (Universitas Nurul Jadid, 2025)
This study aims to analyze the factors that affect prospective students' decision to choose a campus and identify management strategies that can optimize student admissions at STAI Al-Muntahy. The research method used was a mixed method with an explanatory sequential design. Survey and interview data collection techniques. Surveys are used to measure public awareness and interest in institutions. Meanwhile, interviews are used to explain further from the survey results obtained. The findings of this study show several main factors that affect their decision, such as relevant study programs, affordable education costs, and the quality of academic and non-academic services. In addition, innovative, data-based promotions and strengthening the campus's external network also play an important role in attracting the interest of prospective students. The results of this study lead to five main strategies that can be applied to increase new student admissions, namely: (1) more flexible adjustment of education fees, (2) strengthening internal organizations and external campus networks, (3) more targeted and data-driven promotions, (4) improving the quality of academic and non-academic services, and (5) increasing the involvement of alums and the surrounding community. Implementing these strategies is expected to strengthen the image of the campus, increase student satisfaction, and increase the number of new student registrations in the future.